واقع الممارسات المحاسبية في الجزائر في ظل بيئة التحول الرقمي - عماد الدين عوينات (Universty Of El-oued جامعة الوادي, 2024)
الملخص: تهدف هذه الدراسة إلى تحليل واقع الممارسات المحاسبية في الجزائر في ظل ثورة التحول الرقمي. اعتمدت الدراسة على المنهج الوصفي والتحليلي، مستخدمةً أسلوب دراسة الحالة وأسلوب الدراسة الميدانية في الجانب التطبيقي. وتم استخدام أسلوب المقارنة في دراسة حالة بين كل من البيئة المحاسبية الجزائرية والسعودية ودول رائدة في التحول الرقمي. تم استخدام استبانة في الدراسة الميدانية تم توزيعها على 155 فردًا من الأكاديميين والمهنيين لمعرفة آرائهم حول موضوع الدراسة، واستخدمت مجموعة من الأدوات الإحصائية لتحليل البيانات المسترجعة، مثل برنامج (SPSS v25) وبرنامج MINITAB 18. ولقد اظهرت النتائج وجود درجة متوسطة من الوعي بأهمية التحول الرقمي في المجتمع المحاسبي في الجزائر، تمتلك الجزائر بنية تحتية رقمية وجاهزية متواضعة للتحول الرقمي، تواجه الجزائر تحديات كبيرة تؤثر على التحول الرقمي في البيئة المحاسبية، وجود فجوة كبيرة بين استخدام تقنيات التحول الرقمي في المجال المحاسبي بالجزائر مقارنة بالمملكة العربية السعودية والدول الرائدة. Abstract: This study aims to analyse the reality of accounting practices in Algeria in light of the digital transformation revolution. The study relied on the descriptive and analytical approach, using the case study method and the field study method in the applied aspect. A comparative method was used in a case study between the Algerian accounting environment, Saudi Arabia, and leading countries in digital transformation. A questionnaire was used in the field study that was distributed to 155 individuals from academics and professionals to know their opinions on the subject of the study, and a set of statistical tools were used to analyse the retrieved data, such as SPSS v25 and MINITAB 18. The results showed that there is a moderate degree of awareness of the importance of digital transformation in the accounting community in Algeria, Algeria has a digital infrastructure and modest readiness for digital transformation, Algeria faces significant challenges affecting digital transformation in the accounting environment, there is a large gap between the use of digital transformation techniques in Algeria compared to Saudi Arabia and leading countries.
دراسة ميدانية لعينة من الأكاديميين والمهنيين –
أطروحة دكتوراه تخصص محاسبة في العلوم الاقتصادية والتجارية وعلوم التسيير
Keywords: ممارسات محاسبية، نظم معلومات محاسبية، تحول رقمي، حوسبة سحابية، ذكاء اصطناعي; Accounting practices; Accounting Information Systems; Digital Transformation; Cloud Computing; Artificial Intelligence.